2004
DOI: 10.1038/sj.ijo.0802602
|View full text |Cite
|
Sign up to set email alerts
|

Variables predictive of adherence to diet and physical activity recommendations in the treatment of obesity and overweight, in a group of Spanish subjects

Abstract: OBJECTIVE:To assess the factors that could predict a successful completion of a weight loss program. STUDY DESIGN: A single-centered, cross-sectional, prospective study conducted over 4 y. SUBJECTS: Data were obtained on 1018 overweight subjects (788 women, 230 men) aged 14.8-76.3 y (mean 38.4) and body mass index (BMI) of 31.7 (range 25.03-57.1) seeking help to lose weight at a specialist obesity clinic. MATERIALS AND METHODS: A program involving a hypocaloric, Mediterranean diet was prescribed plus recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 30 publications
5
90
1
18
Order By: Relevance
“…Despite the methodological drawbacks of the included trials, yoga can however be preliminarily considered a safe and effective intervention to reduce body mass index in overweight or obese but otherwise healthy adults. It has been shown that while women and younger individuals are less adherent to physical activity interventions targeting overweight and obesity (Bautista-Castano et al, 2004), those individuals are however more likely to practice yoga (Birdee et al, 2008;Cramer et al, 2013e). Thus, yoga can be specifically considered as an alternative to other forms of physical activity for overweight/obese individuals who are not adherent to recommended physical activity regimens.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Despite the methodological drawbacks of the included trials, yoga can however be preliminarily considered a safe and effective intervention to reduce body mass index in overweight or obese but otherwise healthy adults. It has been shown that while women and younger individuals are less adherent to physical activity interventions targeting overweight and obesity (Bautista-Castano et al, 2004), those individuals are however more likely to practice yoga (Birdee et al, 2008;Cramer et al, 2013e). Thus, yoga can be specifically considered as an alternative to other forms of physical activity for overweight/obese individuals who are not adherent to recommended physical activity regimens.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…To date, several studies have provided evidence that high body weight, BMI, or adiposity are associated with lower levels of physical activity participation and lower adherence to activity programs. [3][4][5][6][7][8] The reasons why overweight individuals seem even less willing than normal-weight ones to participate in and adhere to physical activity remain largely unknown despite the obvious practical importance of this question. In the general population, the problem of adherence and dropout is typically approached from the perspective of conceptual models originating in social psychology and general health behavior, none of which take the uniqueness of the physical activity stimulus into account.…”
Section: Introductionmentioning
confidence: 99%
“…Bautista-Castaño et al 25 avaliaram os fatores preditivos da adesão em estudo com 1018 indivíduos que apresentavam excesso de peso inscritos em programa de intervenção nutricional e estímulo à pratica de atividade física. Os autores sugeriram que intervenções com o objetivo de perda de peso e mudança de modos de vida são menos eficazes para indivíduos do sexo feminino, com IMC elevado, mais jovens e que já tentaram perder peso anteriormente.…”
Section: Discussionunclassified